2022
DOI: 10.48036/apims.v18i3.648
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Positron Emission Tomography-Computed Tomography (PET-CT Scan) In Detecting Bone Marrow Involvement in Patients with Diffuse Large B cell Lymphoma

Abstract: Objective: To evaluate the diagnostic accuracy of positron emission tomography combined with CT scan (PET-CT Scan) in detecting bone marrow involvement in patients with diffuse large B-cell lymphoma, keeping bone marrow biopsy as gold standard. Methodology: From November 2017 to May 2018, a cross sectional validation study was carried out at the Aga Khan University in Karachi Department of Oncology's Section of Clinical Hematology. The study comprised a total of 112 patients who were identified as having diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Similarly, another study performed by Cortés-Romera et al [13] showed that PET/CT scan can identify more bone marrow involvement in DLBCL and Hodgkin's lymphoma as compared to bone marrow biopsy with sensitivity, specificity, accuracy, and positive and negative predictive values of 95%, 86%, 87%, and 54% and 99%, respectively. One study from Pakistan by Shaikh et al [19] confers that PET/CT scan can precisely identify bone marrow infiltration in DLBCL patients and has good diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study performed by Cortés-Romera et al [13] showed that PET/CT scan can identify more bone marrow involvement in DLBCL and Hodgkin's lymphoma as compared to bone marrow biopsy with sensitivity, specificity, accuracy, and positive and negative predictive values of 95%, 86%, 87%, and 54% and 99%, respectively. One study from Pakistan by Shaikh et al [19] confers that PET/CT scan can precisely identify bone marrow infiltration in DLBCL patients and has good diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%